Interrelationship and Interdependence Among Macroeconomic Variables in India - Sunil, N.; Purswani, Geetanjali; Benny, Neethu Rose (Arthshastra Indian Journal of Economics & Research, 2019)
India is actively performing on the economic front since the inception of the new economic policy. As it is an open economy, it allows other countries to be a part of its economy. It is pivotal for a country to have coordination among the factors which affect its growth. The study explored the trend and interrelationship among the macroeconomic variables (FDI, FPI, sensex, ER (USD), GDP, and BOP). The quarterly data of six macroeconomic variables were used for the purpose of this study. Trend chart, Augmented Dickey-Fuller Test (ADF), correlation, and regression were put into use to meet the objectives. The results showed that sensex, ER (USD), and GDP were highly correlated. The study also examined the impact of other variables and went on to analyze the impact of other variables on those highly correlated variables. For the data collected, the results showed that GDP and sensex were highly influenced by the FDI, ER (USD), FPI, and BOP; whereas, ER (USD) had no significant impact on the BOP, FDI, and FPI. ER (USD), however, was influenced by GDP and sensex.